TRANSFORMASI PENDIDIKAN ISLAM BERBASIS KEARIFAN LOKAL DALAM MASYARAKAT URBAN MULTIKULTURAL - marwaji, deden; Hikmah, Nur; Andri, Andri (Tarbawi, 2025)
This study examines the transformation of Islamic education through the integration of local wisdom in Lampung within the multicultural suburban context of MA Sunanul Huda Natar. Using a qualitative design, the study explores how the values of piil pesenggiri specifically nemui nyimah and sakai sambaian are integrated into the curriculum and practices of Islamic education. Data were collected through interviews, observations, and documentation analysis. The findings indicate that the integration of local cultural values strengthens students' character formation, enhances contextual understanding of Islamic concepts, and fosters inclusive learning interactions across ethnic groups. Teachers and students demonstrated positive responses to culture-based learning, with increased engagement and relevance of learning activities. Furthermore, the study demonstrates that the multicultural environment of the suburban community supports the development of an adaptive and dialogical model of Islamic education. These results highlight the importance of local wisdom pedagogy as a cultural bridge connecting Islamic values with everyday social realities. This study suggests further exploration of local Islamic pedagogy and the broader application of culture-integrated learning across educational settings.